Classroom Language: Preparing the Pre-Service Teachers for Successful Classroom Interactions - Pusparini, Ririn; Kurniasih, Esti (Jurnal Pendidikan Progresif, 2023)
This study aims to investigate how pre-service teachers (PSTs) employ classroom language for Opening, Running, and Closing the Lesson in the classroom. A qualitative method was applied where the data were gathered through questionnaire sheets and an observation checklist. Thirty students in the second year of the English Education Study Program in Surabaya, Indonesia, participated in this study. The findings reveal that PSTs have applied classroom languages appropriately and successfully for eight components of basic teaching skills. Nevertheless, three components that do not vary are the language expressions attributed to opening the lesson for checking attendance, varying stimuli for setting and cleaning up teaching media, and organizing the small group discussion. The findings can be valuable input for the teacher of an education program to be more concerned with the teacher candidates' language variations to prepare them for successful classroom interactions. Keywords: classroom language, pre-service teachers, classroom interactions.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202304